ANALISIS TERHADAP PERANAN NASYID DALAM DAKWAH - eri satria; Roslan Mohamed (Islam Futura, 2017)
Islamic preaching (dakwa) and nasyid are two elements that have different meaning, but have similarities in purpose, that is to convey the message of Islamic preaching (dakwa). At this time nasyid becomes one of alternatives chosen as a medium to spread propagation through the lyrics of a song presented by a murshid. Thus, nasyid has conveyed messages of Islamic preaching through lyrics of a song indirectly. In this study the authors collected data from several referral sources related to Islamic preaching and nasyid derived from books, journals, and other referral sources related to the title of the study. The study found a relationship between Islamic preaching and nasyid that can be seen in terms of goals. In addition, nasyid also becomes a connection between Islamic preaching and society. It can serve as a medium in conveying Islamic preaching. It cannot be denied that Islamic preaching activities must use various media as a means of delivery Islamic messages. Hence, this study is expected to be input to use nasyid as a medium in conveying Islamic preaching.